Methicillin-Resistant Staphylococcus aureus (MRSA) prevalence in clinical and hospital environmental samples: a review - Tamanna, Sadia; Zareen, Anisa; Islam, Khondoker Rayhanul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.